Screen and triage by community extension workers to facilitate screen and treat: task-sharing strategy to achieve universal coverage for cervical cancer screening in Nigeria (2018)
Purpose Universal coverage of cervical cancer screening remains elusive in most low- and middle income countries (LMICs), home to the greatest burden of this preventable disease. Implementation of a cytology-based screening strategy in these countries is challenging. Also, there is shortage of health care workers (HCWs) to implement the low-technology, cheaper, but equally effective, methods like visual inspection with acetic acid. However, the implementation of HIV programs in LMICs has introduced the innovation of task shifting and task sharing, using the community health extension workers (CHEWs) and community health officers (CHOs) to complement clinical HCWs, especially at the primary health care, level with good outcome. Hence, this study leveraged this strategy. Methods We piloted a study to improve knowledge and practice skills of CHEWs and CHOs in a rural community of Oyo state, Nigeria, through training and participatory supervision to screen for cervical cancer using visual inspection with acetic acid and link positive cases for treatment with cryotherapy. Results A total of 51 HCWs, including doctors, nurses, CHEWs, and CHOs, were trained during the study to provide cervical cancer screening services. After the training, cervical cancer and its prevention knowledge improved from 52.4% before training to 91.5% immediate after training. Over 12 months, 950 eligible women were screened, of whom 848 (89.3%) were screened by CHEWs and CHOs. Of the 63 rescreened by CHEWs and CHOs (data grouped), and nurses, 88.1% and 92.3%, respectively, agreed with expert team review, with κ statistics of 0.76 and 0.84, respectively. Conclusion This pilot project showed the ability of CHEWs and CHOs to identify cervical dysplasiawas good and that of nurses was very good with appropriate competency training to achieve universal coverage of cervical cancer screening in LMICs.